Cultural Identity and Diaspora in Jhumpa Lahiri's The Namesake - Sharmin, Iffat (EAST WEST JOURNAL OF HUMANITIES, 2011)
This paper is an attempt to read Jhumpa Lahiri's The Namesake in the light of Stuart Hall's essay on "Cultural Identity and Diaspora". Hall begins his essay saying that identity is not as transparent or unproblematic as we think it to be and this paper aims to show how the discovery of one's identity is indeed an intricate process, one that is always necessarily complex. When an individual straddles the boundaries of two cultures, as does Gogol Ganguli, the protagonist of The Namesake, the task becomes even more complex and problematic, being grounded in issues of memory, tradition, and family expectations. Throughout the novel, we see that Gogol remains captive to his conflicted identity _ is he Indian or American?- although there is the merest hint at the novel's end that he may choose one identity over the other. His trajectory suggests that, for the second generation Indian_ American at least, refusing to choose one identity over the other, which might mean complete renunciation of either Indian_ness or American_ness, troubles one's negotiation of identity. Whereas Gogol's mother, Ashima, as a first generation Indian_American, is able to negotiate a hyphenated subjectivity because she has an original identity as a starting point, Gogol is 'always_already' in crisis due to his birth on 'foreign' soil. This paper throws light on how Lahiri uses Gogol's name to show the duality of immigrant experience and thus explain what Hall meant by diaspora experience when he said that, "diaspora experience is defined by … the recognition of a necessary heterogeneity and diversity, by a conception of 'identity' which lives with and through, not despite, difference; by hybridity."